2004
DOI: 10.1038/sj.bjc.6602052
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-containing bisphosphonates inhibit cell cycle progression in human melanoma cells

Abstract: Cutaneous melanoma is one of the highly malignant human tumours, due to its tendency to generate early metastases and its resistance to classical chemotherapy. We recently demonstrated that pamidronate, a nitrogen-containing bisphosphonate, has an antiproliferative and proapoptotic effect on different melanoma cell lines. In the present study, we compared the in vitro effects of three different bisphosphonates on human melanoma cell lines and we demonstrated that the two nitrogen-containing bisphosphonates pam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 51 publications
(66 reference statements)
4
29
0
Order By: Relevance
“…It should be noted that cells, exposed up to IC 50 ZOL for 72h, following drug removal later on resume their growth thus indicating the reversibility of the inhibition. In our opinion, this property of ZOL suggests its [23][24][25][26][27]. To date, however, the details of the molecular mechanism of cell cycle arrest involved remain obscure.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It should be noted that cells, exposed up to IC 50 ZOL for 72h, following drug removal later on resume their growth thus indicating the reversibility of the inhibition. In our opinion, this property of ZOL suggests its [23][24][25][26][27]. To date, however, the details of the molecular mechanism of cell cycle arrest involved remain obscure.…”
Section: Discussionmentioning
confidence: 90%
“…These are required for the posttranslational modification (prenylation) of small GTP proteins (such as Rho, Ras, Rac) that play crucial roles in signaling pathways controlling cell growth. The anti-proliferative effect of ZOL was described in several tumor cell lines and it was likely due to cell cycle distribution change by accumulating and arresting cells in the S-phase [23][24][25][26][27]. This arrest was coupled to changing levels of cyclins and cell cycle regulators, and the S-phase arrest was associated with typical (caspase-dependent) [25,27,28] or atypical (caspase-independent) apoptotic pathway.…”
Section: Page 4 Of 38mentioning
confidence: 99%
“…Our observations are in accordance with previously published studies on different types of tumor cells, all suggesting accumulation of ZOL treated cells in S phase. 20,22,23 Kuroda and colleagues 23 reported that ZOL-treated leukemia cells entered apoptosis from the S phase to G2/M boundary. This corresponds with our data demonstrating a distinct loss of G2/M cells at higher ZOL concentrations coinciding with appearance of a sub-G0/G1 peak indicating programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Senaratne et al reported that BP could induce apoptosis in human breast cancer cell lines [17] . Forsea et al also demonstrated that BP had an inhibitory effect in cell cycle progression in human melanoma cells [13] . Furthermore, several studies have demonstrated that alendronate, a BP, could inhibit cell invasion in human epidermoid carcinoma cells [11] and osteosarcoma cells [12] .…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the inhibition of migration or invasion mediated by MMP-2 could be a preventive method of cancer metastasis [9] . Recently, there has been increasing evidence indicating that bisphosphonates (BP) have direct antitumor effects in vivo and in vitro, in addition to their therapeutic antiresorptive properties [10][11][12][13][14][15][16][17][18][19] . For example, Senaratne et al reported that BP could induce apoptosis in human breast cancer cell lines [17] .…”
Section: Introductionmentioning
confidence: 99%